Code Ethics’s Violation of the Republic of Indonesia Audit Board in the Perspective of Independence - Muliawan, Delimukti Putra; Boediningsih, Widyawati (Pusat Kajian Hukum Perbankan Fakultas Hukum Universitas Jember, 2025)
The Supreme Audit Agency of the Republic of Indonesia in implementing the constitutional mandate of the 1945 Constitution Article 23E paragraph (1) is specifically regulated through the Supreme Audit Agency Regulation Number 4 of 2018 concerning the Code of Ethics of the Supreme Audit Agency, the main problems in writing this journal are how the juridical review of the code of ethics of the Supreme Audit Agency of the Republic of Indonesia regarding Independence, how the form of sanctions given to members of the Supreme Audit Agency for violating the Code of Ethics regarding Independence. This research method is normative legal research, this research uses a statutory approach and a concept approach. From the findings in this journal, it is found that independence is needed in producing the Audit Report in accordance with the principles, principles and values of the Supreme Audit Agency.